Zasoby kadrowe polskich schronisk górskich wobec rozwoju turystyki międzynarodowej - Stosik, Aneta; Zarzycki, Piotr (Human resources in polish youth hostels in Sudety mountains in the context of international tourism development, 2006)
The article describes elements of nonmaterial resources management in Polish youth hostels in Sudety Mountains. The article points out need the to change the competition advance strategy which should be based on European Union recommendations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 283-290